2021
DOI: 10.1155/2021/3905353
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Preoperative Fibrinogen‐to‐Prealbumin Ratio in Patients with Stage I–III Colorectal Cancer Undergoing Surgical Resection: A Retrospective Cohort Study

Abstract: Background. The objective of this study was to explore the role of preoperative fibrinogen-to-prealbumin ratio (FPR) in evaluating the prognosis of patients with stage I–III colorectal cancer (CRC). Methods. This retrospective study enrolled 584 stage I–III CRC patients undergoing surgical resection. Logistic regression analysis was used to explore the correlation between FPR and postoperative complications. The Kaplan-Meier curve and Cox proportional hazards model were used to identify the prognostic factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…that FPR can evaluate the prognosis of malignant tumors such as colorectal cancer, hepatocellular carcinoma, esophageal cancer and gastric cancer (13)(14)(15)35). A recent meta-analysis pointed out that high value of FPR is associated with poorer survival and increased risk of recurrence in cancer patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…that FPR can evaluate the prognosis of malignant tumors such as colorectal cancer, hepatocellular carcinoma, esophageal cancer and gastric cancer (13)(14)(15)35). A recent meta-analysis pointed out that high value of FPR is associated with poorer survival and increased risk of recurrence in cancer patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting studies have shown that pre-albumin(PA) and fibrinogen regulate the occurrence and development of various tumors, and their levels in peripheral blood are closely related to the patient's survival and sensitivity to therapy [ 31 , 32 ].As a novel, effective, economical and practical biomarker, the fibrinogen to pre-albumin ratio (FPR) is not only gradually used to evaluate the prognosis of digestive system tumors such as colorectal cancer [ 20 ], hepatocellular carcinoma [ 16 ] and gastric cancer [ 13 ], but also as an index to predict the prognosis of lung [ 33 ] and bladder cancer [ 34 ]. A study of patients with NSCLC reported that FPR is an independent factor affecting OS in patients with advanced NSCLC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Single markers of fibrinogen and pre-albumin are limited and unstable in predicting the prognosis of digestive system tumors [ 13 ]. Hailun Xie et al [ 20 ] found that pre-albumin and fibrinogen themselves do not affect postoperative complications and long-term prognosis of patients with colorectal cancer, while FPR can be used as a predictor of postoperative complications and long-term prognosis of colorectal cancer. FPR can not only reflect the level of inflammation in patients, but also indicate the nutritional status of patients [ 35 ].Patients with high FPR have reduced nutritional levels and a reduced burden of cancer-related inflammation, which can lead to impaired immune detection and recovery [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…All tests were performed within one week before curative surgery as previously described [ 35 , 36 ]. The PNI was calculated as previously described [ 37 ], and patients were divided into PNI-low or -high and DD-low or -high subgroups based on the optimal cutoff points described in the statistical results below. Subsequently, patients were divided into 3 subgroups: PDS 0, PNI low and DD high; PDS 1, PNI/DD low or PNI/DD high; and PDS 2, PNI high and DD low.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, patients were divided into 3 subgroups: PDS 0, PNI low and DD high; PDS 1, PNI/DD low or PNI/DD high; and PDS 2, PNI high and DD low. Additional systematic inflammatory prognostic indicators, such as the neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR) and platelet to lymphocyte ratio (PLR), were also calculated according to a previous report [ 37 ].…”
Section: Methodsmentioning
confidence: 99%